Fluorinated microwave exfoliated graphite oxide: structural features and double layer capacitance. Issue 4 (2nd April 2016) - Khavrel, P. A.; Skokan, E. V.; Rybalchenko, A. V.; Maslakov, K. I.; Chilingarov, N. S.; Baskakov, S. A.; Shulga, Y. M.; Polyakova, M. V.; Goryunkov, A. A.
ABSTRACT: Fluorinated microwave exfoliated graphite oxide (MEGO) samples containing 5.7–29.3 at.% of fluorine were prepared by gas phase treatment of MEGO with XeF2 . According to X-ray photoelectron spectroscopy and infrared spectroscopy data, fluorination of MEGO occurs at C=C bonds while leaving the oxygenated domains intact, and increases the O/C ratio. Cyclic voltammetry studies of fluorination effect on double layer capacitance of MEGO shows 67% growth of its specific capacitance, making such and related carbon materials prospective for supercapacitor applications.